Efektivitas Sponsorship Dalam Meningkatkan Brand Awareness PT. Sentra Timur Residence di Universitas Bakrie (Studi Kasus: Event Maroon Festival 2017) - Hatta, Holila; Muhammad, Arvito (Journal of Entrepreneurship, Management and Industry (JEMI), 2018)
This research aims to examine how the  sponsorship issued by PT. Sentra Timur Residence at Maroon Festival 2017 event in improving brand awareness of Sentra Timur Residence on Bakrie University community. The quantitative approach and survey 103 visitors of Maroon Festival 2017 event as samples collected using convenience sampling technique, and analysed by testing hyphothesis. The result of this research indicates that sponsorship has significant affect on brand awareness. The relationship between sponsorship variables and brand awareness is very strong.